A Nanofibrillated Cellulose/Polyacrylamide Electrolyte‐Based Flexible and Sewable High‐Performance Zn–MnO2 Battery with Superior Shear Resistance. Issue 51 (16th November 2018) - Wang, Donghong; Li, Hongfei; Liu, Zhuoxin; Tang, Zijie; Liang, Guojin; Mo, Funian; Yang, Qi; Ma, Longtao; Zhi, Chunyi
Abstract: There is a growing demand for flexible and wearable energy devices. How to enhance their tolerance to various mechanical stresses is a key issue. Bending, stretching, or twisting of flexible batteries has been widely researched. However, shear force is inevitably applied on the batteries during stretching, bending, and twisting. Unfortunately, thus far, research on analyzing shear resistance of solid batteries or even enhancing the shear tolerance has never been reported. Herein, a sewable Zn–MnO2 battery based on a nanofibrillated cellulose (NFC)/ployacrylamide (PAM) hydrogel, electrodeposited Zn nanoplates anode, and carbon nanotube (CNT)/α‐MnO2 cathode is reported. The designed NFC/PAM hydrogel exhibits a relatively high mechanical strength with a large stretchability; the preformed NFC bone network stabilizes the large pores as channels for electrolyte diffusion. Furthermore, the effect of sewing on enhancing the shear resistance of the solid batteries is analyzed. The sewed Zn–MnO2 battery retains 88.5% of its capacity after 120 stitches, and withstands a large shear force of 43 N. The sewable and safe Zn–MnO2 is also able to be designed into a skirt and put on a toy as an energy source to power a red light emitting diode. Abstract : A safe and sewable battery with high performance is designed based on a nanofibrillated cellulose/polyacrylamide hydrogel electrolyte, carbon nanotube/MnO2 cathode, and electrodeposited Zn anode. Even after being sewed on with 120 stitches, 88.5% capacity is still retained. Through utilizing a sewing method, the assembled batteries exhibit superior shear resistance, up to 43 N.